2016
DOI: 10.1016/j.hkjot.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge of Occupational Therapy among Nigerian Medical and Health Sciences Undergraduates

Abstract: Objective/BackgroundConsequent to the introduction of occupational therapy (OT) training programmes in Nigeria in the past decade, this study sought to assess the awareness and knowledge of Nigerian medical and other health career undergraduates about OT.MethodsThree hundred and eighty-one undergraduates and students of other health disciplines from the College of Health Sciences, Obafemi Awolowo University (OAU), Ile-Ife, Nigeria responded to a validated three section questionnaire assessing their awareness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 13 publications
6
27
3
1
Order By: Relevance
“…This could be because of their lack of knowledge about presence of OTs or about their role in helping patients with occupational performance difficulties. These finding are in line with the previous researches, which found out that most of the physicians and medical students showed lack of knowledge about OTs function and role (13,14,15) . One unexpected finding in the study was that most of HCPs reported that they have heard about OT.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This could be because of their lack of knowledge about presence of OTs or about their role in helping patients with occupational performance difficulties. These finding are in line with the previous researches, which found out that most of the physicians and medical students showed lack of knowledge about OTs function and role (13,14,15) . One unexpected finding in the study was that most of HCPs reported that they have heard about OT.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a large number of participants in this study were from different countries such as India, Egypt and Philippines, which may have more OT services in their home countries. This finding was consistent with the preceding studies (13,15,16) which found that the majority of HCPs had heard about OT but didn't have suitable scientific knowledge. The study has clearly shown that there is a limited knowledge about OT in SA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations